Relationship Of Preparedness With Anxiety For Flood In The Region Of Panjangrejo Village - ika silvitasari; H. Hermawati (Gaster, 2021)
Floods are a type of disaster that people need to be aware of because they can have physical and psychological impacts. One of the impacts of the community on the occurrence of floods is the anxiety of the residents about their unpreparedness for flooding. Objective: to determine the relationship between preparedness and anxiety level in facing floods in Panjangrejo Village. Methods: the research method is a quantitative cross sectional approach with the sampling technique using accidental sampling and get a total sample of 36 respondents. The instrument used to measure preparedness used the adaptation of the 2018 BNPB questionnaire while the level of anxiety used the State Anxiety Inventory (S-AI) Form Y. Results: statistical analysis test used chi square with a significance level of 95%, obtained p value = 0.002 or (p < 0.05), so it is found that there is a relationship between preparedness and level of anxiety in facing floods in Panjangrejo Village. Conclusion: Communities with high preparedness will reduce the level of anxiety, while people with less preparedness will increase the level of anxiety. Suggestion: carry out further research on flood preparedness with a quasi experimental method.